Controlling Singlet Fission in Pendent Acene Polymers - Yablon, Lauren (2020)
Solar energy is a viable alternative to traditional fossil fuel sources. However, single junction silicon solar cells can only efficiently absorb ~30% of available sunlight. A portion of sunlight is too low in energy to be absorbed by the solar cell while another portion of sunlight is too high in energy to be absorbed without losses due to thermalization. Singlet fission, a process that converts a high energy singlet exciton into two lower energy triplet excitons, can be used to convert high energy light into lower energy light that can be absorbed efficiently by silicon. Singlet fission materials that undergo fast singlet fission, have long lived triplets, and have long triplet diffusion lengths show the greatest potential to increase the efficiency of solar cells. This thesis describes the design and singlet fission behavior of norbornene based polymers with pendent acene chromophores. The first chapter highlights other supramolecular singlet fission materials that have been studied to date that served as inspiration for this work. The second chapter demonstrates the efficient singlet fission and the slow, molecular weight dependent triplet recombination that occurs in pendent pentacene polymers. The third chapter outlines how the tunability of the polymer can be used to control singlet fission dynamics. In the fourth chapter, the singlet fission dynamics are shown to be largely unaffected by solvent composition and by casting into thin films. The fifth and final chapter explores exciton migration in pendent tetracene and pentacene block copolymers. This thesis illustrates a new, high tunable platform for studying inter-chromophore singlet fission, which shows promise for use in solar cells.